ACCELERATING STUDENTS MATH PROBLEM SOLVING SKILLS USING THINKING ALOUD PAIR PROBLEM SOLVING (TAPPS) ASSISTED WITH QUIZIZZ - Izzah, Safira Nurul; Alifiani, Alifiani; Ilmi, Yuli Ismi Nahdiyati (Universitas Sembilanbelas November Kolaka, 2024)
The purpose of this study was to describe the implementation of Thinking Aloud Pair Problem Solving (TAPPS) assisted with Quizizz in accelerating mathematical problem solving abilities. The subjects of this study were students of class VIII SMP Negeri 13 Malang consisting of 33 students. This classroom action research was carried out in even semesters with repeated cycles until the indicators of action success were met, each cycle consisting of four stages, namely planning, action implementation, observation, and reflection. The research results in cycle I showed that the results of observation of activity were 79%, the results of observations of student activities were 74.5% and the completeness of learning outcomes reached 63.63% so that they did not meet the indicators of success of the action. In cycle II, the results of observing teacher activity increased by 11.75% to 90.75%, the results of observing student activities increased by 14.25% to 88.75% and the completeness of learning outcomes increased by 18.19% to 81.82% . Based on these results, it can be concluded that the Quizizz-assisted Thinking Aloud Pair Problem Solving (TAPPS) learning model can accelerate the math problem solving abilities of class VIII students of SMP Negeri 13 Malang.